Accumulation of copy-back viral genomes during respiratory syncytial virus infection is preceded by diversification of the copy-back viral genome population followed by selection. Issue 2 (28th September 2022) - Felt, Sébastien A; Achouri, Emna; Faber, Sydney R; López, Carolina B
Abstract: RNA viruses generate nonstandard viral genomes during their replication, including viral genomes of the copy-back (cbVGs) type that cannot replicate in the absence of a standard virus. cbVGs play a crucial role in shaping virus infection outcomes due to their ability to interfere with virus replication and induce strong immune responses. However, despite their critical role during infection, the principles that drive the selection and evolution of cbVGs within a virus population are poorly understood. As cbVGs are dependent on the virus replication machinery to be generated and replicated, we hypothesized that host factors that affect virus replication exert selective pressure on cbVGs and drive their evolution within a virus population. To test this hypothesis, we used respiratory syncytial virus (RSV) as a model and took an experimental evolution approach by serially passaging RSV in immune-competent human lung adenocarcinoma A549 control and immune-deficient A549 Signal transducer and activator of transcription 1 (STAT1) KO cells, which allow higher levels of virus replication. As predicted, we observed that virus populations accumulated higher amounts of cbVGs in the more permissive A549 STAT1 KO cells over time; however, unexpectedly, the predominant cbVG species after passages in the two conditions were different. While A549 STAT1 KO cells accumulated relatively short cbVGs, A549 control cells mainly contained cbVGs of much longer predicted size, which have not been described previously. These long cbVGs were predominant at first in both cell lines in vitro and the predominant ones observed in samples from RSV-infected patients. Although sustained high replication levels are associated with cbVG generation and accumulation, our data show that sustained high levels of virus replication are critical for cbVG population diversification, a process that precedes the generation of shorter cbVGs that selectively accumulate over time. Taken together, we show that selection and evolution of cbVGs within a virus population are shaped by how resistant or permissive a host is to RSV.